Expanding graceful trees - I Nengah Suparta; I Dewa M. Agus Ariawan (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2020)
Two methods for expanding graceful trees are introduced. In constructing a larger graceful trees, these methods are based on a collection of certain graceful trees and one graceful tree as the core of the produced graceful tree.